This preview has intentionally blurred sections. Sign up to view the full version.
View Full DocumentThis preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: Math 25: Advanced Calculus Fall 2010 Homework # 3 – Solutions 1.3.7: Which of the field axioms does Z 6 fail to satisfy? Solution: By observation, Z 6 satisfies A1,A2,M1,M2, and AM1. Furthermore, Z 6 satisfies A3 because 0 + a = a for any a ∈ Z 6 , and satisfies M3 because 1 · a = a for any a ∈ Z 6 . We can check that Z 6 satisfies A4 because: 0 + 0 = 0 = ⇒  0 = 0 1 + 5 = 0 = ⇒  1 = 5 2 + 4 = 0 = ⇒  2 = 4 3 + 3 = 0 = ⇒  3 = 3 4 + 2 = 0 = ⇒  4 = 2 5 + 1 = 0 = ⇒  5 = 1 . However, Z 6 does not satisfy axiom M4 because, for example, 2 does not have a multiplicative inverse: 2 · 0 = 0 2 · 1 = 2 2 · 2 = 4 2 · 3 = 0 2 · 4 = 2 2 · 5 = 4 . 1 1.4.1: Using just the axioms, prove that ad + bc < ac + bd for all a < b and c < d . Proof: Since c < d , axiom O3 implies that 0 < d c . Letting z = d c , x = a , and y = b in axiom O4 tells us that a ( d c ) < b ( d c ) . Applying axiom AM1 and adding ac + bc to both sides of this inequality (which we can do by O3) gives ad ac + ac + bc < bd bc + ac + bc. By commutativity, associativity, and A4, we obtain the desired result. 2 1.4.3: Using just the axioms, prove that for any a > 0 and b > 0 in R , √ ab < a + b 2 . Proof: By axiom O1, we know that either a > b , b > a , or a = b . If a = b , then √ ab = a = a + b 2 and the result is verified. Otherwise, we may assume without loss of generality that a > b . First, we claim that if a > b , then √ a > √ b . We prove this claim by contraposition. Suppose that √ a ≤ √ b . Multiplying both sides of this equation by √ a tells us that a ≤ √ a √ b, by axiom O4. Similarly, multiplyinb both sides of the inequality √ a < √ b by √ b tells us that √ a √ b ≤ b, again by O4. By transitivity, this implies that a ≤ b , which establishes the claim. Next, since √ a > √ b , axiom O3 implies that √ a √ b > 0. Using problem 3.1(I), we compute < ( √ a √ b ) 2 = a 2 √ a √ b + b. By axiom O3, we can add 2 √ a √ b to both sides of this equation to obtain 2 √ a √ b < a + b. ( * ) First of all, we notice that √ a √ b = √ ab . Second of all, by Problem 3.1(II), we know that 1 > 0, and hence 2 = 1 + 1 > 0 + 1 = 1 by O3. Therefore 2 > 0 as well. By Problem 3.1(III), it follows that 1 2 > 0 also. Therefore, by axiom O4, we can multiply both sides of equation (*) by 1 2 to obtain the desired result....
View
Full Document
 Fall '10
 StevenKlee
 Calculus, Real Numbers, upper bound, Axiom

Click to edit the document details